Exploratory analysis of demographic data, tobacco habits, and oral health-related quality of life among complete denture patients - Shankar Iyer; Sunil Dhaded; Manupreet Kaur; Prashant Hegde (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study assessed the impact of demographics and tobacco habits on oral health related quality of life (OHRQoL) among complete denture patients. Setting and Design: Prospective cohort study design. Materials and Methods: Two hundred and eighty four edentulous patients, aged above 30 years, were chosen as the sample for the study after taking informed consent. Information regarding demographic data and smoking status was obtained from each participant. OHRQoL was evaluated using the Oral Health Impact Profile Edentulousness (OHIP EDENT) quantifying various domains, namely functional limitation, physical pain, psychological discomfort, physical disability, psychological disability, social disability, and handicap. Statistical Analysis Used: Data were analyzed using the Statistical Package for the Social Sciences version 23.0 (IBM; Chicago, Illinois, USA). Mann-Whitney U test was applied to find significant differences in OHRQoL between gender, age, and smoking status. P < 0.05 was considered to be statistically significant. Results: It was seen that complete denture wearers above 65 years had higher OHIP EDENT scores as compared to younger counterparts suggesting the compromised quality of life in the functional domain which was statistically significant. Psychological discomfort was greater in females while physical disability seemed higher in males. Smoking was found to be a factor associated with decreased OHRQoL. Conclusion: Older age groups, female gender, and smoking were factors associated with decreased OHRQoL among complete denture patients.